Factor Analysis of the Parent Experience of Racial Socialization Scale. (June 2014) - Thomas, Anita Jones; Blackmon, Sha'Kema; Speight, Suzette L.; Hewitt, Amber; Witherspoon, Karen M.; Selders, Michael
This investigation examined the factor structure and validity evidence for the Parent Experience of Racial Socialization Scale (PERS). Exploratory factor analysis found four interpretable factors accounting for 40% of the variance in the racial socialization construct. The identified factors were religion and spirituality, alertness to discrimination, mainstream, and cultural pride and coping. Correlation analyses indicated negative relationships between the newly identified PERS factors religion and spirituality and alertness to discrimination and the Teenagers Experiences of Racial Socialization (TERS) factor Alertness to Discrimination. In contrast, a positive relationship was found for the PERS spirituality and religion factor and the TERS cultural endorsement of the mainstream factor. Recommendations for research methods regarding racial socialization scales are provided.